Control interno y su incidencia en la gestión administrativa y financiera de la empresa manjimexport s.a., del cantón Buena Fe, año 2023. - Jiménez Zambrano , Mayerli Ximena (2025)
This research evaluates the impact of internal control on the administrative and financial management of the Ecuadorian company MANJIMEXPORT S.A., located in the Buena Fe canton and dedicated to the export of cocoa. Several deficiencies in internal procedures were identified, such as an outdated control manual, a lack of effective supervision, and poor staff training, which negatively impact operational efficiency and the reliability of financial information. To address this problem, a mixed-method approach was applied, utilizing qualitative techniques such as interviews, direct observation, and document review, as well as quantitative techniques such as surveys and analysis of financial indicators. The research design was descriptive, explanatory, and diagnostic, allowing for a comprehensive understanding of the internal control system and its influence on decision-making. This evaluation was structured within the framework of the 2013 COSO Model, which establishes five fundamental components: control environment, risk assessment, control activities, information and communication, and supervision. The findings reveal that the internal control system presents significant flaws in administrative and financial management, affecting the company's profitability and sustainability. It was also found that inefficient compliance with operating procedures weakens process traceability and limits the company's ability to respond to financial risks.